Adaptacija funkcional'nogo rezerva trenirovannosti ženšcin-bokserov razlicnoj kvalifikacii k trenirovocnym nagruzkam centralizovannoj podgotovki - Domuladžanova, O. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
This article discusses the problems of adaptation of the cardiovascular system of elite female boxers, different age groups to exercise centralized training loads. The technique of calculation of functional reserve of trained athletes, computer-based modification of results HR and ad, developed in the FNC RAMS VNIIFK. Depending on the measurement results received, software methodology automatically generates personalized advice on best, at this point of time, physical activity training classes. As a result of the research, the dynamics of functional reserve of trained female boxers of different skills in microcycles of centralized training.